2017
DOI: 10.11114/jets.v5i3.2095
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Table Tennis Trainings on Certain Physical and Physiological Parameters in Children Aged 10-12

Abstract: In the research it was aimed to examine the effects of basic table tennis trainings, which were implemented on girls aged 10-12 for 16 weeks, on certain physical and physiological parameters.A total of 40 students, as randomly selected 20 test groups and 20 control groups at an age range of 10-12 participated in the research. These students were first applied pre-test measurement, and final test measurement was performed following application of basic table tennis trainings for 16 weeks.Statistical analysis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Since table tennis is numbered among one of the fastest ball games in the world [ 13 , 15 ], a major part of studies have focused on strategies of visual search [ 30 ]. Other studies have shown that table tennis can also improve the dynamic visual acuity (DVA) of the general population [ 31 ], the biomotor capacities of children in general [ 32 ] and static balance of deaf children [ 33 ]. It is easy on the joints and rarely becomes traumatic [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Since table tennis is numbered among one of the fastest ball games in the world [ 13 , 15 ], a major part of studies have focused on strategies of visual search [ 30 ]. Other studies have shown that table tennis can also improve the dynamic visual acuity (DVA) of the general population [ 31 ], the biomotor capacities of children in general [ 32 ] and static balance of deaf children [ 33 ]. It is easy on the joints and rarely becomes traumatic [ 25 ].…”
Section: Introductionmentioning
confidence: 99%